My age of anxiety eaudiobook Fear, hope, dread, and the search for peace of mind. - Stossel, Scott (Random House Audio, 2014)
A riveting, revelatory, and moving account of the author’s struggles with anxiety, and of the history of efforts by scientists, philosophers, and writers to understand the condition   As recently as thirty-five years ago, anxiety did not exist as a diagnostic category. Today, it is the most common form of officially classified mental illness. Scott Stossel gracefully guides us across the terrain of an affliction that is pervasive yet too often misunderstood. Drawing on his own long-standing battle with anxiety, Stossel presents an astonishing history, at once intimate and authoritative, of the efforts to understand the condition from medical, cultural, philosophical, and experiential perspectives. He ranges from the earliest medical reports of Galen and Hippocrates, through later observations by Robert Burton and Søren Kierkegaard, to the investigations by great nineteenth-century scientists, such as Charles Darwin, William James, and Sigmund Freud, as they began to explore its sources and causes, to the latest research by neuroscientists and geneticists. Stossel reports on famous individuals who struggled with anxiety, as well as on the afflicted generations of his own family. His portrait of anxiety reveals not only the emotion’s myriad manifestations and the anguish anxiety produces but also the countless psychotherapies, medications, and other (often outlandish) treatments that have been developed to counteract it. Stossel vividly depicts anxiety’s human toll—its crippling impact, its devastating power to paralyze—while at the same time exploring how those who suffer from it find ways to manage and control it. My Age of Anxiety is learned and empathetic, humorous and inspirational, offering the reader great insight into the biological, cultural, and environmental factors that contribute to the affliction.